PROJECT-BASED LEARNING (PJBL): ENHANCING STUDENTS’ SPEAKING SKILLS - Sari, Ika Purnama; Syafitri, Nining; Faridha, Noor; Khairas, Eri Ester; Siregar, Epi Supriyani; Purba, Anita; Sormin, Rizky Khairunnisa (JURNAL EDUSCIENCE, 2025)
Purpose–This study aims to measure the effectiveness of implementing Project-Based Learning (PjBL) in improving students' speaking skills.Methodology – This study uses a quantitative pre-test and post-test design. Researchers will compare students' speaking skill scores before (pre-test) and after (post-test) using the Project-Based Learning (PjBL) to determine whether there is a significant improvement. The quantitative data will analyse used SPSS to measure the experimental and control classes.Findings – This study show that the experimental class had a higher average score (75.74) than the control class (61.32). The Sig. (2-tailed) is less than 0.05; the difference between the means is statistically significant. There is a statistically significant difference between the means of the experimental and control classes.Contribution – The increase in scores from pre-test to post-test is empirical evidence that project-based learning is an effective learning method for improving student learning outcomes while developing the various skills required for future success.